ANALISIS PEMANFAATAN HUTAN MANGROVE DAN PERAN STAKEHOLDERS DI KABUPATEN INDRAMAYU - Nur Ikhsanudin; Cecep Kusmana; Sambas Basuni (JURNAL AGRICA, 2018)
Increasing aquaculture is not accompanied by the sustainability of mangrove forests which are ecosystems along the coast of Indramayu. This research aims to estimate the extent of existing mangrove forest, to identify of mangrove forest utilization, to analyze the interests and influence of stakeholders involved in the management and utilization of mangrove forest in Indramayu Regency. The methods used are desk study, observation, and interview. Primary data were obtained from interviews with semi-structured interviews. The data were analyzed using stakeholders analysis methods. The primary data also obtined is Landsat 8 OLI image data recorded in June 2017. Secondary data is obtained from OPD in several maps type, regulation documents and main task of OPD. Spatial analysis compares the existing land cover with forest area maps and Spatial Plan. The result of the research shows that the area of mangrove vegetation cover is 2,228,79 Ha. There are 27 stakeholders involved in mangrove forest management in Indramayu Regency. The results of stakeholder mapping indicate that there are six stakeholders in the quadrant subject (high interest, low influence), eight stakeholders in the key player quadrant (high interest, high influence), eleven in the crowd quadrant (low interest, low influence), and one stakeholder in the quadrant context setters (low interest, high influence).Keyword: interest, mangrove, utilization, influence, stakeholders